2011
DOI: 10.1016/j.chembiol.2011.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Osteoclastogenesis Inhibition by a Novel Class of Biphenyl-Type Cannabinoid CB2 Receptor Inverse Agonists

Abstract: The cannabinoid CB(2) receptor is known to modulate osteoclast function by poorly understood mechanisms. Here, we report that the natural biphenyl neolignan 4'-O-methylhonokiol (MH) is a CB(2) receptor-selective antiosteoclastogenic lead structure (K(i) < 50 nM). Intriguingly, MH triggers a simultaneous G(i) inverse agonist response and a strong CB(2) receptor-dependent increase in intracellular calcium. The most active inverse agonists from a library of MH derivatives inhibited osteoclastogenesis in RANK liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 50 publications
4
63
1
Order By: Relevance
“…These observations emphasize that the concept of functional selectivity also applies to inverse agonists, in that both compounds are similarly effective inverse agonists in guanosine 5Ј-O-(3-thio)triphosphate binding assays (Ross et al, 1999). These data also support the differences (Schuehly et al, 2011) observed between SR144528 and AM630. However, the lack of effect of AM630 on CB 2 surface levels seems to contradict the Grimsey et al (2011) report, for unclear reasons.…”
Section: Drugsupporting
confidence: 78%
See 1 more Smart Citation
“…These observations emphasize that the concept of functional selectivity also applies to inverse agonists, in that both compounds are similarly effective inverse agonists in guanosine 5Ј-O-(3-thio)triphosphate binding assays (Ross et al, 1999). These data also support the differences (Schuehly et al, 2011) observed between SR144528 and AM630. However, the lack of effect of AM630 on CB 2 surface levels seems to contradict the Grimsey et al (2011) report, for unclear reasons.…”
Section: Drugsupporting
confidence: 78%
“…Each ligand differed in its rank order of potency in the three assays despite similar efficacies. Schuehly et al (2011) recently described a case of functional selectivity of CB 2 ligands. AM630 displayed inverse agonist/antagonist actions on CB 2 -mediated inhibition of cAMP production and was silent in its effects on intracellular calcium transients.…”
Section: Drugmentioning
confidence: 99%
“…Previous studies revealed that 4-O-methylhonokiol potently inhibited neuroinflammatory responses and was associated with cognitive enhancement in AD animal models. The antiinflammatory activity was mediated by diminishing NF-jB signaling pathway (Lee et al 2012a (Schuehly et al 2011). They suggest that the effects of the compound on CB 2 receptors are associated with anti-neuroinflammatory effects, since the receptors are primarily associated with a broad range of inflammatory processes (Gertsch & Anavi-Goffer 2012).…”
Section: Magnolia Extract 4-o-methylhonokiol and Obovatolmentioning
confidence: 98%
“…However, activation of CB 2 receptors in the BV2 microglial cell line inhibits adenylyl cyclase (Franklin et al, 2003). A particularly interesting example is the natural product 49-O-methylhonokiol, which shows inverse agonism for cAMP production and agonism for release of intracellular calcium (Schuehly et al, 2011).…”
Section: Adenylyl Cyclasementioning
confidence: 99%